Total Hip or Knee Arthroplasty in Patients with a History of Native Joint Septic Arthritis: A Meta-analysis and Systematic Review of Risk Factors of Prosthetic Joint Infection - Sanka, Sravan Kumar; Tahir, Muhammad; Lakpriya, Sathya; De, Chiranjit; Oni, Tofunmi; Pierce, Todd P. (Clinics in orthopedic surgery, 2025)
Background: Septic arthritis is a debilitating diagnosis, and many of these patients elect to undergo total knee arthroplasty (TKA) and total hip arthroplasty (THA). The purpose of this systematic review and meta-analysis is to assess the risk of prosthetic joint infection (PJI) in those who undergo primary TKA or THA with a history of septic joint arthritis. Secondarily, we will evaluate patientspecific or surgical factors that could increase the risk of primary arthroplasty failure. Methods: A comprehensive search of PubMed, CINAHL Plus, Embase, and Scopus was performed. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed for study selection, data extraction, and analysis. From a total of 404 articles, 18 studies were selected for inclusion. Results: Our final cohort consisted of 1,758 arthroplasties with Staphylococcus species (n = 375 cases, 40%) being the most common causative septic arthritis agent. Male sex (70.5% vs. 51.1%, p = 0.0003) and Gram-negative bacteria cause (11.6% vs. 6.0%, p = 0.02) were associated with an increased risk of PJI following arthroplasty. There was no association found between arthroplasty failure and increasing age or body mass index. There was no difference in PJI rates between 1- and 2-stage arthroplasty (10.9% vs. 10.8%; p = 0.47). Conclusions: Male sex and resistant organism as causes of septic arthritis were associated with an increased risk of PJI in patients with a history of native septic arthritis. Single- and 2-stage procedures had similar success rates. Future studies should be larger and focus on long-term outcomes in these patients. KCI Citation Count: 0